EEG Biomarkers in Children and Adolescents With Feeding and Eating Disorders: Current Evidence and Future Directions - Berchio, Cristina; Cambi, Susanne; Pappaianni, Edoardo; Micali, Nadia (Frontiers in Psychiatry, 2022)
Introduction. Electroencephalography (EEG) represents a powerful tool to detect abnormal neural dynamics in child and adolescent psychiatry. Feeding and Eating Disorders (FEDs), such as anorexia nervosa (AN), bulimia nervosa (BN), binge eating disorder (BED), and avoidant restrictive food intake disorder (ARFID) onset in childhood and adolescence. EEG has rarely been used to examine cortical brain activity in children and adolescents with FEDs. This review aims to summarize EEG findings in FEDs amongst children and adolescents, and to highlight areas deserving further research. Methods. We searched the literature for EEG studies on children and adolescents with FEDs using Google Scholar, PsycINFO, Medline, and PubMed. Results. Twelve studies were identified, the majority focusing on AN (N=10). The identified studies suggest reduced action monitoring control (preparatory waves, N200, P300), specific perceptual-cognitive styles to body/face perception (late positive potentials/early posterior negativity), as well as fundamental changes in posterior theta oscillations in AN. Behavioral traits of BN/BED (i.e. loss of control eating, emotional eating), and AN seem to be associated with an increased attentional reactivity (P300) to visual food stimuli. Conclusion. EEG research in children and adolescents with FEDs is limited and mostly fo-cused on AN. While EEG abnormalities seem consistent with a reduced top-down control and attentional allocation deficits in AN, altered attention specific to food cues emerges across FEDs. Overcoming conventional EEG analyses, and investigating spatial properties (i.e., elec-trical neuroimaging), will enhance our understanding of FEDs neurobiology.